Special physical fitness control in Japanese athletes - Sterkowicz, S.; Sogabe, A.; Sterkowicz-Przybycien, K.; Maehara, K.; Sasaki, T. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
Physical fitness is one of the important factors affecting the quality of the tactical and technical activities in judo. This study aimed to further knowledge of: 1) body stance side preferred in performing tachi-waza (fighting in standing position); 2) level of fitness preparation of males and females; 3) effect of the dominant body side on the quality of performance in Special Judo Fitness Test (SJFT) and the effort perceived.